Peningkatan Aktifitas dan Hasil Belajar Mahasiswa Pendidikan Kimia Melalui Presentasi tugas dengan Sistem Kepala Bernomor Pada Mata Kuliah Kimia Dasar II - Elva Yasmi; Sri Haryati (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2012)
Lecturing activities in the campus should be in the form of student-centeredlearning, in which lecturers as the educators have a role to facilitate the learning activities tobe optimally running. However, the low activity of students has an impact on the learningoutcomes. One of the efforts to improve the students’ activities in learning is byimplementing the task presentation with the numbered-head system. Through this activity, itis expected that the students’ activity in the classroom would significantly improve andwould impact the learning out comes. This research has been applied in two cycles on theeven semester of 2010/2011 in the class of B2 (Non-Regular) Chemistry EducationDepartment. The result of the research showed that there was a significant improvement onstudents’ activities from 68,9 % in the cycle 1 up to 70,3 % in the cycle 2. The impact onstudents’ learning outcomes was also increased, from the average of 46,20 up to 66,47. Thestudents were in the perception of strongly agree (3,34) on the treatment given, therefore, theefforts on improving students’ learning activities and learning outcomes could be achieved.